2019
DOI: 10.11118/actaun201967051369
|View full text |Cite
|
Sign up to set email alerts
|

IFRS 16 and its Impacts on Aviation Industry

Abstract: Current differences between the accounting models for a financial and an operating lease and their critics from the users of the financial statement forced the IASB issued a new Leases Standard, IFRS 16, which supersedes IAS 17 Leases and its related interpretations in January 2106. IFRS 16 will eliminate dual accounting model for lessees and it is assumed to have significant business implications, especially from lessee’s point of view. The paper focuses on quantification of the impact of IFRS 16 on selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
3
6
0
4
Order By: Relevance
“…Researchers took 15 European airlines as sample of the study. Veverková (2019) found that after the implementation of IFRS, there was a significant difference in financial ratios indicating profitability as measured by ROA and ROE and leverage. The implementation of these IFRS made a significant difference to leverage.…”
Section: Previous Researchmentioning
confidence: 99%
“…Researchers took 15 European airlines as sample of the study. Veverková (2019) found that after the implementation of IFRS, there was a significant difference in financial ratios indicating profitability as measured by ROA and ROE and leverage. The implementation of these IFRS made a significant difference to leverage.…”
Section: Previous Researchmentioning
confidence: 99%
“…La discusión sostenida por diversos organismos emisores de normas para reformar este modelo se ha realizado durante ya varias décadas (Mellado & Parte, 2017;Morales-Diaz, 2018;Veverková, 2019). El primer borrador de una nueva norma de arrendamientos fue emitido por el IASB en el año 2010, para luego -en enero de 2016-emitir la norma definitiva (Morales-Diaz, 2018), la cual obliga a tener en cuenta y reconocer en el balance, tanto los arrendamientos financieros como los operativos.…”
Section: Orígenes De Niif 16 Arrendamientosunclassified
“…Considerando que tanto activos, pasivos y patrimonio tuvieron variaciones debido a la primera aplicación de NIIF 16, los indicadores de liquidez, rentabilidad y endeudamiento se ven afectados en diversos sentidos, dependiendo del indicador, tal como se expone y explica en la tabla 5. Lo anterior está en línea y viene a ratificar lo mencionado en diversos estudios (Arrozio et al, 2016;Giner et al, 2019;Morales-Diaz, 2018;Morales-Diaz & Zamora-Ramirez, 2018b;Nurkasheva et al, 2018;Veverková, 2019;Zamora-Ramirez & Morales-Diaz, 2018).…”
Section: Tabla 1 Composición Industrial Según Ipsa En Chile Año 2020unclassified
“…Kesimpulan tersebut juga serupa dengan hasil penelitian sebelumnya pada perusahaan minyak dan gas di Nigeria menunjukkan bahwa Aset sewa (Finance lease & Operating lease) memiliki dampak positif signifikan terhadap ROA (Bello et al, 2016). Penelitan lain pada perusahaan penerbangan di Republik Ceko menunjukkan bahwa kapitalisasi aset sewa memberikan dampak signifikan pada profitabilitas yang diwakili oleh ROA (Veverková, 2019).…”
Section: Pembahasanunclassified